Kesadaran, Norma Subjektif, Pembebasan Bea Balik Nama Kendaraan Bermotor, Pemutihan Pajak dan Kepatuhan Wajib - Prayoga, I Kadek Cesin Dwi Murthi; Jati, I Ketut (E-Jurnal Akuntansi; Vol 33 No 6 (2023)DO - 10.24843/EJA.2023.v33.i06.p06, 2023)
The research aims to obtain empirical evidence on the influence of taxpayer awareness, subjective norms, exemption from Motorized Vehicle Title Transfer Fee (BBNKB), and Motorized Vehicle Tax (PKB) bleaching on motorized vehicle taxpayer compliance in Bangli Regency. The research location is the SAMSAT Joint Office, Bangli Regency. Determination of the sample using accidental sampling method. The total sample of 100 respondents was determined using the Slovin formula. Data was collected through a survey method using a questionnaire. The data analysis technique uses multiple linear regression. The results showed that taxpayer awareness, subjective norms, BBNKB exemption, and PKB bleaching had a positive effect on motor vehicle taxpayer compliance in Bangli Regency. Keywords: Subjective Norms; BBNKB Exemption; Whitening; Taxpayer Compliance